Conservation of the Vulnerable sarus crane Grus antigone antigone in Kota, Rajasthan, India: a case study of community involvement - Kaur, Jatinder; Nair, Anil; Choudhury, B.C. (Oryx, 2008)
The sarus crane, a bird species characteristic of wetlands, is categorized as vulnerable on the IUCN Red List. In India, sarus cranes occur mostly outside protected areas and use these unprotected areas for feeding and breeding. They are consequently threatened by poaching and the destruction of their eggs and juveniles. To protect the crane's habitat and nests a community education and awareness campaign was carried out, using audiovisual shows and presentations, in villages and schools in the vicinity of sarus crane nesting sites in Kota district, Rajasthan. In 2004–2005 protection of 22 nests by volunteer Rural Village Sarus Protection Groups, formed as a result of the campaign, resulted in the successful fledging of 19 chicks, including some in the dry season. Our experience with this project demonstrated that it is possible to re-establish a bond between farmers and nature, and work on community involvement for the sarus crane is continuing, with the involvement of more districts in Rajasthan.